Inhibiting Factors of Cost Performance in UAE Construction Projects - Ahmed Marey Alhammadi, Ahmed Salem; Memon, Aftab Hameed (International Journal of Sustainable Construction Engineering and Technology, 2020)
UAE construction industry frequently faces poor cost performance which commonly known as cost overrun problem. This problem is resulted from several factors and it is important to identify these cost overrun factors in order to avoid and minimize it. Hence, this paper focused on determined the relevancy of factors affecting cost performance in construction projects of UAE. Through a review of past research works conducted globally, 27 factors of cost overrun were listed and used for developing a structured questionnaire. A survey was conducted with 33 practitioners from client, consultant and contractors organizations involved in handling construction projects in UAE. The respondents were requested to state their perception regarding the relevancy of each of the factors that was perceived in context with cost overrun issue using 5-points Likert scale. The responses were analysed using average index method and the results found that all the 27 factors are relevant with construction industry of UAE in causing cost overrun. These factors can be used for further investigation to uncover critical problems of cost overrun.